Interference of weeds in ruziziensis grass pastures - Pinheiro, Guilherme Henrique Rodrigues; Araújo, Prissila Pereira dos Santos e; Marques, Ricardo Fagundes; Souza, Rodrigo Marques de; Silva, Ilgner Thiago Duarte; Marchi, Sidnei Roberto de (Acta Scientiarum. Animal Sciences, 2022)
The aim of this study was to assess the effect of increasing periods of coexistence of weed plants with Urochloa ruziziensis on the canopy structure and productivity of a pasture already established with this forage species. The experiment was a randomized blocks design with four replications, and treatments consisted of seven increasing periods of coexistence of forage grass with weed plants: 0 (control), 15, 30, 45, 60, 75 and 90 days after regrowth (DAR). The main morpho-structural and productive characteristics of the forage plants were determined at the end of the experimental period (90 DAR). The ratio of the first green leaf height to the tiller height increases, while the leaf to stem ratio diminishes as the period of interaction with the infesting community increases. The number of green leaves per tiller and the tiller height diminishes as the period of coexistence with weed plants increases. The presence of weed plants interferes negatively with all parameters of the grass canopy structure and productivity of a grazing land already established with Urochloa ruziziensis, suggesting that measures of control of the infesting community should be adopted up to 17 days of regrowth of the forage plant.